Betalains as Natural Dyes and Applications - Fauziah, Tasya; Suryani, Okta (Sains Natural: Journal of Biology and Chemistry, 2024)
Betalains are natural pigments that include betacyanin and betaxanthin, found in plants such as beets and cacti. In the food industry, betalains are used as natural colorants due to their color stability and health benefits, including antioxidant and anti-inflammatory properties that support the prevention of degenerative diseases. With increasing demand for natural ingredients, betalains are also being promoted in the cosmetics and health product industries. In the healthy food sector, new extraction techniques like microwave-assisted extraction and aqueous two-phase technology have improved the purification efficiency and quality of betalain pigments. In cosmetics, betalains are utilized as anti-aging and anti-inflammatory components, with innovative approaches like biopolymer encapsulation to enhance product stability. Geographical trends show significant interest in betalain use in natural cosmetics and healthy foods in Europe and Asia, while research in Latin America focuses on its potential as a supplement and food colorant. In renewable energy technology, betalains act as photosensitizers in dye-sensitized solar cells (DSSCs), though their stability still requires optimization, such as through co-sensitization with other pigments. These innovations suggest that betalains hold considerable potential in the food, cosmetics, and energy industries, making them a versatile and globally relevant natural material.